Thin Capitalization, Transfer Pricing Aggresiveness, Penghindaran Pajak - Falbo, Teza Deasvery; Firmansyah, Amrie (Indonesian Journal of Accounting and Governance, 2018)
The increase in tax revenue in Indonesia is not accompanied by an increase in tax ratio The low tax ratioindicatestax avoidance practices in Indonesia. Some tax avoidance practices can be conductedthrough transferpricing and thin capitalization.This study is aimed to examine empirically the effect of thin capitalization as well astransfer pricing aggressiveness on tax avoidance practice in Indonesia. This study uses manufacturing companieswhich are listed on Indonesia Stock Exchange (IDX) within the period 2013-2015. Using purposive sampling, theselected samples in this study are 90 companies, so the total sample is 270 samples. The hypothesis examinationused in this study is multiple linear regression analysis of panel data.The results of this study suggest that thincapitalization is positively associated with tax avoidance, while transfer pricing aggressiveness is not associated withtax avoidance.